Aplikasi Hybrid Contract pada Produk MJB: Studi Multiakad di BMT Nusantara Capem Kencong - Lutfianah Putri; Uliyatul Mu’awwanah (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
Islamic financial institution BMT (Baitul Maal wat Tamwil) develops a range of solutions to address the intricate requirements of its clients. The contract, or akad, is an essential document in muamalah transactions since it sets forth the rights and responsibilities of the parties involved. So, Islamic financial institutions, especially BMT, need to innovate, be progressive, and dynamic by upgrading their muamalah contracts so they can compete with mainstream financial institutions' goods. The use of hybrid contracts to fund savings products is one example of this kind of innovation. Therefore, the author is keen to investigate whether or not BMT UGT Nusantara Branch Kencong's contracts are legitimate. The researchers at BMT UGT Nusantara Branch Kencong set out to learn more about hybrid contracts, which include more than one contract. In order to bring theory and practice into harmony, this study employs a qualitative methodology that combines primary and field data. Scholars approve of these hybrid contracts, according to the results, provided they don't go against Sharia norms and principles. To prevent unfair treatment of individuals, these hybrid contracts aim to define rights and responsibilities more precisely. It follows that purchasing MJB items via hybrid contracts at BMT Nusantara Branch Kencong is lawful and in accordance with Sharia law. In addition, both BMT and its clients may benefit from muamalah via these hybrid contracts.